2014
DOI: 10.1007/s00421-014-2986-7
|View full text |Cite|
|
Sign up to set email alerts
|

Variants within the MMP3 gene and patellar tendon properties in vivo in an asymptomatic population

Abstract: Patellar tendon properties do not seem to be influenced by the MMP3 gene variants measured. Although these MMP3 gene variants have previously been associated with the risk of tendon pathology, that association is unlikely to be mediated via underlying tendon dimensional and functional properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…Several SNVs (rs591058, rs650108 and rs679629) in the MMP3 gene (chromosome 11) have been reported to be associated with Achilles tendinopathy, whereas neither patellar tendon properties nor our results on patellar tendinopathy were found to be influenced by the same variants.…”
Section: Discussioncontrasting
confidence: 64%
“…Several SNVs (rs591058, rs650108 and rs679629) in the MMP3 gene (chromosome 11) have been reported to be associated with Achilles tendinopathy, whereas neither patellar tendon properties nor our results on patellar tendinopathy were found to be influenced by the same variants.…”
Section: Discussioncontrasting
confidence: 64%
“…Our results showed that there is a weak association between MMP-3 SNPs and OA susceptibility. Although these gene variants were previously associated with cartilage and tendon pathology risk, no association between MMP-3 SNPs and the degeneration of knee articular cartilage or patellar tendon have been reported [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, regarding musculoskeletal soft tissue injuries such as anterior cruciate ligament injury and Achilles tendon injury, several studies have reported that the association between genetic polymorphisms and injuries in case-control association analysis (2832). In addition to these case-control association studies, other studies have investigated the functional role of injury-related genetic polymorphisms (3335). On the other hand, although the details of specific genetic polymorphisms as determinants for muscle injury risk are gradually being elucidated (3644), the sample sizes of previous studies have been relatively small (54–257 athletes).…”
Section: Discussionmentioning
confidence: 99%